THEMATIC RICHNESS IN THE STORIES OF AYŞE KİLİMCİ - GEZER, Alpay (Atlas Journal, 2020)
The themes discussed in the narrative texts evolve from abstraction to concreteness by being connected to a certain time, place and people within the framework of an event. Thus, the conceptual framework with thematic abstraction has a concrete structure and existence. The richness and density of the theme, which is the very heart of the literary text, stand out in the text with other structural elements of the text. Revealing the thematic richness in literary works is the most important starting point in revealing the value and message of the works. Ayşe Kilimci, one of the acclaimed names of Turkish storytelling with her unique style and original expression, is a writer who expresses social problems with an artist sensitivity, and in the valleys of language and literature, seeks solutions to the problems she sees in the society. Ayşe Kilimci, who has seven printed story books; has created theme-rich works such as women, children, love, death, migration, education, urbanization, poverty, sexuality, art, injustice, generational conflict, marriage, housing problem, moral, and social and cultural corruption. In the present study, it was aimed to determine the prominent elements of the thematic richness of her stories by analysing the stories in Kilimci’s printed story books from a thematic aspect employing the document analysis method.